ANALYZING THE LEVEL OF HIGH TROPOSPHERC OZONE DURING THE SUMMER 2013 IN SKOPJE, R. MACEDONIA - Stoimenovski, Bobi; Mitreski, Kosta; Naumoski, Andreja; Davchev, Dancho (My University, 2016)
Ozone is a health-hazardous air pollutant and its level is increased with increasing of the air temperature. In this paper, we have analyzed the summer period from 01.06.2013 to 30.09.2013 in Skopje, R. Macedonia. The influence of the environmental parameters to the ozone level was determined by applying the decision trees. The main objective of this research is to determine the threshold temperature value(s) for which the high ozone values will exceed the limit values. According to different types of decision trees, we found the temperature thresholds of 30.15oC, which resulted in the highest ozone levels.
Keywords: threshold ozone, decision tree, environmental parameters, troposphere